Perfil de pacientes intoxicados investigados no estado de Goiás entre os anos 2007 a 2012 - Oliveira, Flávia Neri Meira de (2017)
Introduction: Substance, of easy access to the population, as cleaners’ substances, cosmetics, medicines and chemical’s industries products are examples for sources of intoxications. Toxicological Information Centers (CITs) informs about intoxications and register the cases in information systems (SINAVISA). The evaluation of a big data need care, because to be accomplished its necessary the use of statistics methods to monitor constantly of a big data. Objective: To perform quality control of data in variables product and “chemistry group”, and to evaluate the profile of intoxications of patients notified in SINAVISA, during the period of 2007 to 2012. Methodology: In the first moment it was evaluated the cadasters in variables product and “chemistry group” with Textual Analysis. Posteriorly was evaluated variables of 5041 investigations files of intoxications by medicines and 16333 investigations files of intoxication by medicines, cosmetics, toxic plants, cleaners’ substance, chemical’s industries products, rodenticides, foods, abuse drugs, vets products and agrotoxics, except files from intoxication by venomous’ animals, with Multiple Correspondence Analysis (MCA) and Hierarchical Cluster Analysis (HCA). Results: It was observed the presence of discordances on data of product and “chemistry group” and then corrected. In analysis of medicine observed that, children and women are the principal victims of intoxication by medicines. The “chemical groups” that more affected on children with 1 to 4 years old was antibiotics, anti-inflammatories not steroidal, antipsychotics, adrenergics agonists, hormones and anti-histaminics. The children with less than one-year-old presented intoxication with ignored products, antibacterial, sympathomimetics agonists, antagonists and anti-inflammatories. Patients with age of 20 to 29 years, female gender, intoxicated by anxiolytics, antidepressives and anticonvulsants. Analysis of 16333 investigations files observed that severe intoxications are in chemical’s group agrotoxics, as pyrethroids, organophosphates, glycine, coumarins and carbamates. The ignored products were grouped in clusters with tendency to more severity. Children with age less than 4 years old also intoxicated with acids, rodenticides, and agrotoxics, but with less frequency. Conclusion: The method was capable of corrected the errors presents in variables “chemical group” and product. Additionally, it was traced the following profile: children intoxicated with medicines antibiotics, anti-inflammatories not steroids, antipsychotics, adrenergics agonists, hormones and anti-histaminics, and young adults intoxicated with agrotoxics, rodenticides and medicines anxiolytics, anti-depressives and anticonvulsants.